As razões africanas para não cooperar com o Tribunal Penal Internacional: análise do impacto das abordagens políticas sobre o desempenho da organização - Dias, Taynara Samantha (2020)
This study has as research theme the International Criminal Court and the political issues it is involved due to the political nature of its orders, its actions and the crimes under its jurisdiction. This characteristic is considered to put it in a dilemma, generating conflicts with other states that fear its political agency. This is the condition of relations between the Court and some African states. As the Court has neither function nor capacity to exercise the search and the arrest of the accused itself, the Court depends on the collaboration of other States; however, there are many states that do not establish cooperative relations. Perceptions of inequality, injustice and imperialist actions by the Court may be some of the reasons that affect relations between these states and the International Criminal Court. Therefore, it is sought to study the reasons of some African States for non-cooperation, considering the cases of Omar al-Bashir, from Sudan, and Uhuru Kenyatta, from Kenya, in order to understand the weight on the ICC of state tension regarding collaboration.